Relevance of Imaging Examinations in the Surgical Planning of Patients with Bowel Endometriosis. (January 2016) - Trippia, Carlos H.; Zomer, Monica T.; Terazaki, Carlos R.T.; Martin, Rafael L.S.; Ribeiro, Reitan; Kondo, William
Endometriosis is a benign gynecologic disease characterized by the presence of endometrial tissue outside the uterine cavity. The complexity of the disease results from its multiple clinical presentations, the multifocal pattern of distribution of the lesions, the presence of extra pelvic sites of the disease (mainly affecting the urinary and the intestinal tracts), and the difficulty in the preoperative diagnosis (by means of imaging studies) and in the surgical treatment. The preoperative mapping of the lesions, either by ultrasound or by magnetic resonance imaging, allows for an adequate surgical planning and a better preoperative patient counseling, especially in those women with deep infiltrating endometriosis affecting the bowel. Also, the choice of the surgical team that is going to perform the procedure may be based on the preoperative workup. In this paper, we highlight the important findings that should be described in the imaging examination reports for the preoperative workup of patients with deep infiltrating endometriosis of the intestine.